The critical role of HR in managing stress and enhancing wellbeing in the age of digitalization - Louati, Hanen; Saidi, Khadija; Bouslimi, Jihen; Sayari, Sonia; Aljohaini, Amal (Frontiers in Sustainability, 2026)
In digitally transforming and increasingly complex organizational environments, employee wellbeing has emerged as a strategic imperative for sustainable performance. This study draws on the Job Demands–Resources (JD-R) model to examine how sustainable Human Resource Management (HRM) practices can mitigate workplace stress and promote psychological wellbeing in the context of rapid digitalization. Specifically, it investigates the role of perceived organizational support and transparent advancement pathways as key resources that help employees manage elevated job demands. Through a quantitative study involving 206 employees across government, semi-government, and private organizations in Saudi Arabia—a national context undergoing significant digital reform—the proposed model is empirically tested. Findings reveal that excessive workload and work–family conflict are strongly associated with increased stress, which in turn negatively affects mental health and overall wellbeing. Conversely, supportive organizational climates and clear career development structures serve as protective factors. These results highlight the importance of human-centric HR strategies in digitally evolving workplaces, offering both theoretical insights into the JD-R framework and practical guidance for designing inclusive, wellbeing-oriented systems as a foundation for innovation and long-term success.